2000
DOI: 10.15760/etd.2398
|View full text |Cite
|
Sign up to set email alerts
|

Staying on Script: Sexual Scripts and Sex Education

Abstract: Existing research suggests that men and women develop differing sexual scripts that influence their behavior, interactions and emotions regarding sex. The objective for this project is to examine the experiences of men and women with formal sex education programs, especially in regards to information about: anatomy and biology, sexual responsibility and risk taking, sexual desire, virginity and abstinence, as well as to explore sources of sex education outside of school. Several studies suggest masculine sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…The focus on heteronormative sex education can impede sexual minority students from learning about safe sexual practices that are congruent with their sexual identities and/or behaviors (Formby, 2011;Hauck, 2015). The lack of inclusion of sexual minority identities in formalized sex education can also lead to higher occurrences of negative mental health outcomes including depression and suicidal ideation (Blake et al, 2001;Lindley & Walsemann, 2015;Pound et al, 2016).…”
Section: Impact Of Abstinence Only Until Marriage and Heteronormativementioning
confidence: 99%
See 1 more Smart Citation
“…The focus on heteronormative sex education can impede sexual minority students from learning about safe sexual practices that are congruent with their sexual identities and/or behaviors (Formby, 2011;Hauck, 2015). The lack of inclusion of sexual minority identities in formalized sex education can also lead to higher occurrences of negative mental health outcomes including depression and suicidal ideation (Blake et al, 2001;Lindley & Walsemann, 2015;Pound et al, 2016).…”
Section: Impact Of Abstinence Only Until Marriage and Heteronormativementioning
confidence: 99%
“…Fisher (2009) concluded that gay and bisexual individuals are unable to form positive sexual identities in non-inclusive sex education programs like AOUM. The inability to form a positive identity can lead individuals to even question their own mental health due to the lack of normalization of sexual identities not congruent with heteronormative expectations (Hauck, 2015;Pound et al, 2016).…”
Section: Impact Of Abstinence Only Until Marriage and Heteronormativementioning
confidence: 99%
“…Other studies have researched formal sex education offered to the youth in schools. Hauck (2015) examined the experiences of men and women with school-based sex education programmes in regard to sexual scripts offered to them during sex education sessions. Few studies have focused on sex education offered by the church to the youth.…”
Section: Theoretical Frameworkmentioning
confidence: 99%